Effects of Social Media use on Depression in Adolescents - Hassan Raza, Mansoor Ahmad, Mudassir Mahdi, Muhammad Aaqib Sajjad, Ali Hassan Sajjad, Ahmed Hassan Usman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Depression is a psychological disorder which impairs your mental health in a negative way and in extreme cases it also causes physical symptoms. There are many cases of depression. Overall prevalence of depression is about 50%1. Aim: To determine relationship among social media use and depression in adolescents. Study Design: cross sectional study Methods: Sample size was calculated with epitool calculator. Sample size will be 323 by using finite population of 1000 with 95% confidence interval and 5% level of significance. All students of a particular semester (convenient sampling) was enrolled for this study. The students were asked to fill questionnaire which contains scale PHQ-9 (Patient health questionnaire-9) a valid scale to measure depression2,3. Data was gathered and analyzed by SPSS version 23 for results. Result: 351 people participated in this survey, mean age was 21.58 SD 2.46, male to female ratio was almost equal. Average timing of social media use was(3h15mins) (SD=1.42), 82 people was suffering from mild depression, 166 with moderate depression, 75 people have moderately severe depression and 8 people was found to have severe depression scoring. Finally, no of hours people using social media was tested against depression in the form of chi-square value which was significant. Conclusion: It was observed in this study that people using social media are prone to develop depression because they self-compare themselves to other people; however, this relationship was not linear to inference any exact limit of social media use. Depression Could be due to other causes due to physical and mental effects of computers and mobile phone use.